Jugamos delante de y detrás de - Cruz Lizana, Luz Miguelina (2018)
Nowadays we know that each person is a complex and complete being composed of different dimensions (body, mind and emotions) which do not operate independently and disconnected from each other, but are interconnected all the time in each moment and circumstance of the life Psychomotricity is a discipline that looks and understands the human being as a being integrated between his mind, thought and emotions (Psyche) and his body, movement and action (motor). Children use much their body to interact and know the world around them so, they need to run, jump, touch, feel among other body actions, so the body, emotion and learning are found intimately linked in the development of children. Spatial development in children is very important because it helps to maintain the constant localization of the body in both in the performance of the position of objects in space and to place those objects according to their own position. The development of spatial notions in Children condition their location in the environment in which they find themselves and their learning in school and for life. Psychopedagogy affirms that the development of space in children conditions the index in a very straight way in literacy and mathematics, therefore it is important that parents and teachers become facilitators in order to stimulate and favor the development in the space By performing psychomotor activities, they will help the child in his motor expressivity, involving the emotions and feelings and the affective area, providing a harmonious growth in children. In today's education teachers have the task of achieving the comprehensive and optimal development of children using resources and strategies that allow them to discover themselves and their environment in a motivating way.